2021
DOI: 10.3390/ijfs9040074
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ownership Structure and Board Characteristics in Stock Market Liquidity

Abstract: Corporate governance plays a significant role in the value of shareholders and share prices, hence stock market liquidity is affected. Previous research has mainly focused on the issue in developed markets, whereas in developing countries there is a need to analyze the influence of corporate governance on stock market liquidity. Therefore, the present study aims to examine the impact of ownership structure and board characteristics on stock market liquidity of non-financial firms of South Asian countries such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 73 publications
(99 reference statements)
3
14
0
Order By: Relevance
“…This indicates that the higher the board size, the higher the stock market liquidity. This is consistent with the findings of Daadaa (2021) and Abbassi et al (2021), and is also in line with the debate that larger boards have more resources to monitor managerial performance and have skills to form various effective committees, allocate specific tasks, and facilitate greater debating on corporate issues. This can lead to greater information transparency (Anderson et al, 2004;Klein, 2002).…”
Section: Board Structure and Stock Market Liquiditysupporting
confidence: 88%
See 3 more Smart Citations
“…This indicates that the higher the board size, the higher the stock market liquidity. This is consistent with the findings of Daadaa (2021) and Abbassi et al (2021), and is also in line with the debate that larger boards have more resources to monitor managerial performance and have skills to form various effective committees, allocate specific tasks, and facilitate greater debating on corporate issues. This can lead to greater information transparency (Anderson et al, 2004;Klein, 2002).…”
Section: Board Structure and Stock Market Liquiditysupporting
confidence: 88%
“…That is, board size is positively correlated with stock liquidity. Abbassi et al (2021) also indicated that board size has a positive effect on stock liquidity. Based on the arguments above, the following hypothesis is developed: H1: Board size improves stock liquidity.…”
Section: Board Size and Stock Market Liquiditymentioning
confidence: 98%
See 2 more Smart Citations
“…Gul et al (2011) also state that female directors expect higher monitoring levels, in the form of auditing, than their male colleagues. (Abbassi et al, 2021) conducted Research stated that the large board of directors enhances stock liquidity because board members play vital monitoring role to reduce information asymmetry and eventually helping to enhance stock liquidity. Mbanyele (2021) argued that board networks enhances stock liquidity more via the information channel when economic policy uncertainty is high.…”
Section: Board Characteristics and Stock Liquiditymentioning
confidence: 99%